Obsessive-Compulsive Disorder Associated with Posterior Cranial Fossa Meningioma - Nobuyuki Takeuchi; Etushi Kato; Kousuke Kanemoto (Case Reports in Psychiatry)
We report here a patient in whom the effects of a cerebellum mass may have led to development of obsessive-compulsive disorder (OCD). A 33-year-old woman showed symptoms of OCD, including obsessive worry about infection from tainted blood and repetitive confirmation, which worsened during pregnancy. She had comprehension in regard to her illness and no evidence of cognitive dysfunction and did not meet other DSM-5 criteria such as depression. One month after giving childbirth, the symptoms worsened, while headache and dizziness also developed. The Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) score was 34. The patient was examined for a headache and a posterior cranial fossa meningioma was found. Following resection of the meningioma, the OCD symptoms were remarkably reduced (Y-BOCS score 10). There is only one previous report of pure OCD associated with a cerebellar mass and the present findings should help to elucidate the mechanism.